Endovascular Embolization by Parent Artery Reconstruction of a Symptomatic Fusiform Posterior Cerebral Artery Aneurysm Using Onyx HD‐500: A Neurointerventional Report. Issue 4 (14th January 2013) - Bogason, Einar T; Patel, Akshal S; Cockroft, Kevin M
ABSTRACT BACKGROUND AND PURPOSE Posterior cerebral artery aneurysms are treatment challenge for the neurosurgeon. Parent artery occlusion, trapping and bypass have been the classic treatment options for aneurysms in this location. With the introduction of newer embolic agents such as Onyx®, endovascular intervention is now a viable therapy for these aneurysms. CASE SUMMARY We report the case of a 60‐year‐old man who presented with a symptomatic, though unruptured, fusiform left posterior cerebral artery aneurysm. Given the distal location of this dominant sided aneurysm, post‐operative visual deficits and aphasia were a concern if parent vessel occlusion were to be performed. Therefore, an endovascular reconstruction using Onyx HD‐500 and two closed‐cell stents was performed. CONCLUSIONS This report illustrates the ability of a high‐density liquid embolic agent to provide immediate reconstruction of a fusiform aneurysm in a distal location.